TUNDRA-TAIGA BIOLOGY: HUMAN, PLANT, AND ANIMAL SURVIVAL IN THE ARCTIC. Robert M.M. Crawford. 2013. Oxford: Oxford University Press. 270 p, softcover, illustrated. ISBN 978-0-19-955940-4. £75.00 – ERRATUM. (10th April 2015) - Turunen, Minna T.
Abstract : The price and ISBN in the book review (Turunen, 2014 ) refer to the hardcover of the book. The price of the softcover is £37.50 with the ISBN 978-0-19-955941-1. We apologise for this mistake.